Becoming a business journalist in Malawi: a case study of The Daily Times and The Nation newspapers - Manjawira, Ellard Spencer (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2010)
In the past few decades, the proportion of business news compared to general news has increased tremendously across all media platforms in Africa. While the critical role played by business journalism is recognised, little is known about the people who write and report such news. Most studies on business reporting have tended to focus on analysing the content of business news, rather than the specific processes through which business journalists are socialized and trained. The findings of this study are drawn mainly from in-depth interviews with business reporters and editors at two leading newspapers in Malawi, The Daily Times and The Nation. Three major findings emerge trom the study data. First, business journalists vary in their educational and professional backgrounds, as well as the reasons for working on this beat. Second, the majority of them have no prerequisite formal education and training in business journalism and, therefore, have little knowledge and skills about what constitute good business journalism. Third, professionalism in the sub-field is constrained by a host of factors, influence of advertisers being the critical one. The study recommends that business reporting become an integral component of journalism education and training programmes to adequately prepare future generations of business journalists. In addition there is need for media houses to devise strategies to counter obstacles that business journalists face for them to effectively contribute to political economy debate.,KMBT_363
Keywords: Journalists -- Malawi; Journalism -- Study and teaching -- Malawi; Journalists -- Training of -- Malawi; Journalists -- Education -- Malawi